Evaluation of the Performance of Floating Fiber Embankment Models for Tidal Flood Mitigation in Coastal Areas: Contributing to SDG 11 - Sunaryo Sunaryo; Imam Wahyudi; Moh. Faiqun Ni'am (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: To evaluate the development of floating fiber embankment technology as an innovative solution for mitigating tidal flooding in coastal areas of Indonesia, particularly along the northern coast of the Java Sea. The proposed system is designed to automatically adapt to tidal level fluctuations, addressing challenges related to land subsidence and sea level rise. Method: The study employed a combined simulation and laboratory experimental approach to analyze the performance of the floating fiber embankment. Numerical simulations were conducted to evaluate the structural behavior under hydrostatic pressure, while laboratory testing was performed using a scaled physical model to validate the simulation results. Results: The findings indicate that the floating fiber embankment demonstrates stable structural performance under tidal loading conditions. The maximum recorded deformation was 0.0043 meters, with a maximum stress of 8.231 × 10⁶ Pa and a strain of 0.00045. These results confirm that the structure can maintain elasticity and structural integrity under hydrostatic pressure. Novelty: The application of adaptive floating fiber embankment technology that can automatically adjust to tidal fluctuations as a sustainable alternative to conventional static embankments. This system provides an effective and efficient solution to reduce the impact of tidal flooding in coastal regions while advancing SDG 11 (Sustainable Cities and Communities) by strengthening coastal resilience and supporting sustainable flood mitigation efforts.